2023
DOI: 10.3389/fped.2023.1213072
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral scanners in children: evaluation of the patient perception, reliability and reproducibility, and chairside time—A systematic review

Diego Serrano-Velasco,
Andrea Martín-Vacas,
Marta M. Paz-Cortés
et al.

Abstract: PurposeThe aim of this systematic review is to evaluate the perception of the patient, the chairside time, and the reliability and/or reproducibility of intraoral scanners for full arch in pediatric patients.MethodsA data search was performed in four databases (Medline-Pubmed, Scopus, ProQuest and Web of Science) in accordance with the PRISMA 2020 statements. Studies were classified in three categories (patient perception, scanning or impression time and reliability and/or reproducibility). The resources, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Concerning clinician-centred outcomes, a critical factor to consider is the comparative accuracy of digital and conventional impressions in infants with CLP. The findings of this systematic review, indicating comparable accuracy between digital and conventional impressions in infants with cleft lip and palate (CLP), are consistent with prior research that has indicated the potential of digital impressions in paediatric dentistry [ 45 ]. Nevertheless, the precise manner in which scanning techniques, such as the utilisation of a variety of scanners and scanning strategies and the implementation of smaller scanning tips, affect the accuracy of digital impressions remains uncertain, particularly with regard to their effect on the trueness and precision components of accuracy [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 86%
“…Concerning clinician-centred outcomes, a critical factor to consider is the comparative accuracy of digital and conventional impressions in infants with CLP. The findings of this systematic review, indicating comparable accuracy between digital and conventional impressions in infants with cleft lip and palate (CLP), are consistent with prior research that has indicated the potential of digital impressions in paediatric dentistry [ 45 ]. Nevertheless, the precise manner in which scanning techniques, such as the utilisation of a variety of scanners and scanning strategies and the implementation of smaller scanning tips, affect the accuracy of digital impressions remains uncertain, particularly with regard to their effect on the trueness and precision components of accuracy [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 86%
“…The aim of the study was to evaluate the comfort of children and adolescents with intraoral scanning procedures compared to the conventional method by comparing a widely used and studied scanner (iTero TM ) with another recently commercialized one (Primescan TM ). As reported in recent systematic reviews, intraoral scans seem to be a promising method for both adult [12] and pediatric [20] patients. Although children and adolescents make up most patients susceptible to orthodontic treatment, many studies conducted on perception, comfort, and preference have been performed on adult patients [3,4].…”
Section: Discussionmentioning
confidence: 79%